Digital product innovation management: Balancing stability and fluidity through formalization - Robin Pesch; Herbert Endres; Ricarda B. Bouncken (Journal of Product Innovation Management, 2021)
While an increasing body of research is considering the role of digital product innovation for firms' survival, there is still a dearth of studies on how firms can best pursue digital product innovations. The development of these innovations is often accompanied by uncertainty and ambiguity. Thus, firms might benefit from the greater clarity and guidance that result from formalization. However, the application of formalized procedures and structures might also lead to the suppression of fluidity, creativity, or change. Therefore, the purpose of this study is to determine if formalization at the project level can enhance digital product innovation. A partial duality logic integrating evidence of both the positive and negative effects of formalization builds the fundament for the hypothesized model. We use survey and patent data for a sample of 395 firms operating in the manufacturing industry to test the model. The results suggest the diminishing marginal utility of formalization—that is, formalization enhances digital product innovation radicalness and digital product innovation performance but with decreasing positive marginal returns. These findings challenge the widespread assumptions on the relationship between formalization and innovation. This new perspective on the relationship between formalization and innovation helps identify conditions in which formalization can facilitate firms' efforts to develop profitable, innovative digital products. For example, the results demonstrate that older firms in particular can benefit from formalization. In turn, beyond providing insights for executives, this study offers answers to persistent research questions concerning which organizational arrangements are optimal for enhancing digital product innovation.
Keywords: 650; age; digitalization; digital innovation; duality; formalization; innovation performance; product innovation management; radicalness